Non-planar tetrathiafulvalene derivative modified hole transporting layer for efficient organic solar cells with improved fill factor. (August 2021) - Zhao, Min; Li, Yuexing; Liu, Le; Zhao, Chengjie; Jiu, Tonggang; Hu, Minjie; Xiao, Xunwen
Graphical abstract: Highlights: TTF-pm was used as buffer layers in PTB7-Th:PC71BM organic solar cells for the first time. The device based on these bilayered HTLs yielded a notably high FF of 74.05%. The TTF-pm film can also be employed in PM6:Y6 non-fullerene solar cells as a result of efficient interfacial modification. Abstract: Interface engineering has been widely proved to be an effective approach to improving the overall efficiency of organic solar cells (OSCs). Among the enhanced photovoltaic parameters, a high fill factor (FF) is more responsible for a stable and efficient device. Herein, a simple and effective strategy with a view to improving the FF is demonstrated by modification of hole transporting layers (HTLs). By using a non-planar conjugated tetrathiafulvalene derivative (named TTF-pm) and poly (3, 4-ethylenedioxythiophene): polystyrene sulfonate (PEDOT:PSS) as double HTLs, the conventional device based on PTB7-Th:PC71 BM bulk heterojunction delivers a boosted power conversion efficiency (PCE) of 9.80% and an impressive FF of 74.05%. The analyses presented indicate that the enhanced FF is mostly attributed to the optimized morphology of active layer, improved mobility and suppressed charge recombination via interfacial modification. Moreover, the device stability is also improved benefiting from the optimized film morphology. In addition, a PCE of 16.5% for non-fullerene organic solar cells based on PM6:Y6 blend film using the new HTLs is obtained, which is 7.8% higher than the control. This study highlights the potential of TTF derivatives as new HTLs for high and stable performance in the field of organic photovoltaics.